THE INFLUENCE OF FOOD & BEVERAGE QUALITY, SERVICE QUALITY, PLACE, AND PERCEIVED PRICE TO CUSTOMER SATISFACTION AND REPURCHASE INTENTION - BERLIANSYAH, REZHA ARLANDA; SUROSO, AGUS (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
This type of the research is case study with survey method by using questionnaire as a toolof data collection. The study was conducted in Purwokerto area. There are many varioustype of culinary business, such as cafe, restaurant, foodstreet, foodcourt, etc. But one of themost popular in the society now is cafe and restaurant. One of the new cafe and resto thathad been just found in Purwokerto is Level Up. As a new arrival, Level Up have a uniqueconcept, place, foods and beverages, and also the services that can attract young adult inPurwokerto to visit Level Up. But, there was a decrease in the customers who visited LevelUp after a year of standing and the problem that faced by Level Up become a businessphenomenon. Based on the problems above, this research was conducted to analyze thefood and beverage quality, service quality, place, and perceived price to customersatisfaction and repurchase intention. Respondents of this research are 165 respondentscame from consumers in Purwokerto who have been visited Level Up Purwokerto. Thisresearch uses SEM (Structural Equation Model) as analysis tools technique. Statisticalsoftware SPSS is used to analyze the data. The result of hypothesis testing using T-test is inthe following: (1) Food and beverage quality has positive effect on customer satisfaction. (2)Service quality has positive effect on customer satisfaction. (3) Place has a positive but nosignificant effect on customer satisfaction. (4) Perceived price has a positive effect oncustomer satisfaction. (5) Customer satisfaction has a positive effect on repurchaseintention.